Isaacs’ syndrome-possible etiopathogenesis and clinical aspects: a case report - Liyanage, L. R. Sathisha Deshan; Patel, Grishma Rajendrakumar; Sergeevna, Malevskaya Alexandra (International Journal of Research in Medical Sciences, 2024)
Isaacs’ syndrome (IS) is a rare condition which is characterized by peripheral nerve hyperexcitability which is due to continuous motor activity. The exact etiology for this condition is unknown yet there are several etiopathologies like autoimmune, genetic, or hereditary which can be an etiology for the IS. In our case report the likely etiology is autoimmune. Its clinical feature includes fasciculation, myokymia, and hyperhidrosis. To confirm the diagnosis mostly imaging methods of examination are performed like MRI, ultrasound, and EMG. In our patient MRI and EMG examination was performed. There are no particular therapeutic treatments that can help in this condition only symptomatic treatment can be delivered. Plasma exchange has a promising outcome for a momentary. In our case report, we propose the possible etiology of the condition.